Srpski - Sučević, Nikola J.; Gligorov, Saša; Stojanović, Zoran (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
This paper analyses the influence of the current transformer saturation due to high fault currents on secondary current waveform and analyses the operation of differential protection under those conditions. Analysis are performed on relay software model, as well as on the relay itself by injecting currents on relay inputs using test set. The comparison of behavior of software model and physical relay has been performed. Network modeling has been performed in DIgSILENT PowerFactory and relay testing using DOBLE test set.
Keywords: current transformer saturation; transformer differential protection; software simulations; relay testing